Vital ministry issues Examining concerns and conflicts in ministry - Zuck, Roy B. (Grand Rapids, MI Kregel resources, 1994)
Includes bibliographical references.
Series produced to commemorated the 150th anniversary of Bibliotheca sacra (1843-1993) and the diamond anniversary (1934-1994) of Bibliotheca sacra's association with Dallas Seminary. Each volume in the Vital issues series includes Bib. sac. articles from the thirties to the present.
Keywords: Pastoral theology; Clergy -- office